1998
DOI: 10.1016/s0092-8674(00)81703-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of WUSCHEL in Regulating Stem Cell Fate in the Arabidopsis Shoot Meristem

Abstract: The shoot meristem gives rise to the aerial parts of higher plants by continuously initiating new organs. The basis of this activity is its ability to maintain a pool of pluripotent stem cells, which are the ultimate source of all tissues of the shoot. In Arabidopsis plants mutant for the WUSCHEL (WUS) gene, the stem cells are misspecified and appear to undergo differentiation. Here, we show that WUS encodes a novel homeodomain protein which presumably acts as a transcriptional regulator. The pattern of WUS ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
1,339
1
35

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,511 publications
(1,466 citation statements)
references
References 54 publications
49
1,339
1
35
Order By: Relevance
“…WUSCHEL ( WUS ) is a homeodomain TF that is expressed in flower and shoot meristems, where it induces stem cell fate in a non‐cell‐autonomous manner (Laux, Mayer, Berger, & Jurgens, 1996; Mayer et al., 1998). Overexpression of WUS in arabidopsis is sufficient to induce organogenesis and SE in the shoot and root tip (Chatfield et al., 2013; Gallois, Nora, Mizukami, & Sablowski, 2004).…”
Section: A Network Of Arabidopsis Transcription Factors Controls Somamentioning
confidence: 99%
“…WUSCHEL ( WUS ) is a homeodomain TF that is expressed in flower and shoot meristems, where it induces stem cell fate in a non‐cell‐autonomous manner (Laux, Mayer, Berger, & Jurgens, 1996; Mayer et al., 1998). Overexpression of WUS in arabidopsis is sufficient to induce organogenesis and SE in the shoot and root tip (Chatfield et al., 2013; Gallois, Nora, Mizukami, & Sablowski, 2004).…”
Section: A Network Of Arabidopsis Transcription Factors Controls Somamentioning
confidence: 99%
“…The class I KNOX genes, which include STM, BP, KNAT2, and KNAT6, are also implicated in SAM function (Lincoln et al, 1994;Long et al, 1996;Semiarti et al, 2001). The WUSCHEL (WUS) is required for stem cell function in the SAM (Laux et al, 1996;Mayer et al, 1998). The CLA-VATA3 (CLV3) is involved in restricting stem cell population in the SAM by negatively regulating WUS (Brand et al, 2000;Schoof et al, 2000).…”
Section: Ectopic Expression In 35s::cuc1 Seedlings Of Genes Involvedmentioning
confidence: 99%
“…The pga6 mutant was found to efficiently produce somatic embryos on seedlings and explants in the presence of the inducer. Molecular analysis demonstrated that PGA6 was identical to the homeobox gene WUSCHEL (WUS) [21], which regulates stem cell fate in shoot and floral meristems [23][24][25]. Moreover, ectopic expression of WUS also induces shoot and floral stem cell activities in roots and stems, respectively [26,27].…”
Section: Introductionmentioning
confidence: 99%